1997
DOI: 10.1080/01635589709514494
|View full text |Cite
|
Sign up to set email alerts
|

Tea and cancer prevention: An evaluation of the epidemiologic literature

Abstract: Animal and in vitro studies provide evidence of an anticarcinogenic potential of active ingredients in teas. This review encompasses epidemiologic studies of stomach, colon, and lung cancer as well as the evidence of a relationship between tea drinking and cancer at large in humans. Cohort studies do not suggest a protective role for tea drinking in the total risk of cancer. Site-specific studies reveal a more complex picture. The epidemiologic studies on tea drinking and stomach cancer do not justify claims o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
90
0
1

Year Published

1997
1997
2012
2012

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 185 publications
(93 citation statements)
references
References 22 publications
2
90
0
1
Order By: Relevance
“…It was suggested that the protective effect of tea may depend on the different etiological factors involved in different cancer types and even for the same cancer types in different geographical areas. Similar conclusions have been reached in subsequent reviews [59][60][61][62].…”
Section: Studies On Tea and Human Cancersupporting
confidence: 74%
“…It was suggested that the protective effect of tea may depend on the different etiological factors involved in different cancer types and even for the same cancer types in different geographical areas. Similar conclusions have been reached in subsequent reviews [59][60][61][62].…”
Section: Studies On Tea and Human Cancersupporting
confidence: 74%
“…Red wine is one of the best known such drinks (Maxwell et al, 1994;Whitehead et al, 1995), and the green tea favored by Orientals also contains high level of antioxidants. A few epidemiologic studies have reported that the incidence of coronary heart disease and cancer decreased with intake of green tea (Bushman, 1998;Kohlmeier et al, 1997;Stoner & Mukhtar, 1995) and that the oxidation of low density lipoprotein was suppressed with green tea in vitro (Luo et al, 1997). However, the studies dealing with in vivo increase of antioxidant effects of green tea are rare (Benzie et al, 1999;Pietta et al, 1998;Sera®ni et al, 1996).…”
Section: Introductionmentioning
confidence: 99%
“…The relationship between tea consumption and colorectal risk has been studied by many investigators, but no clear-cut conclusions can be drawn (reviewed in (Blot et al, 1996;Kohlmeier et al, 1997;Bushman, 1998;Landau et al, 2005). Sun et al recently conducted a meta-analysis on 21 relevant papers published up to January 2005 (Sun et al, 2006b).…”
Section: Human Studiesmentioning
confidence: 99%